2001
DOI: 10.1046/j.1365-3083.2001.00862.x
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus Interferes with the Innate Response to Bacterial Products in Human Whole Blood by Attenuation of IL‐10 Production

Abstract: Current immunosuppressive strategies are aimed at abrogating the allospecific T‐cell response against donor tissues or organs. However, little information is yet available on the potential influences of these drugs on innate immune responses. In order to address this, we have employed a whole blood model. Human whole blood was pretreated with sirolimus, cyclosporine A or tacrolimus in therapeutic as well as supra therapeutic doses, and subsequently stimulated with lipopolysaccharide (LPS), peptidoglycan (PepG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 54 publications
3
22
0
Order By: Relevance
“…The combination of immunosuppressive drugs required for preventing rejection of allogeneic hepatocytes in our studies was similar to that required previously in solid organ allografts, 21 despite the differences in immune responses elicited by solid organ or cell allografts. 22 Although most current immunosuppressive drugs do not specifically target cell subsets regulating the adoptive immune system, 23,24 we found that pharmacological regulation of the innate immune system benefited transplanted cell engraftment. It is noteworthy that the major fraction of transplanted hepatocytes is cleared intravascularly even before cells enter the liver parenchyma.…”
Section: Discussionmentioning
confidence: 80%
“…The combination of immunosuppressive drugs required for preventing rejection of allogeneic hepatocytes in our studies was similar to that required previously in solid organ allografts, 21 despite the differences in immune responses elicited by solid organ or cell allografts. 22 Although most current immunosuppressive drugs do not specifically target cell subsets regulating the adoptive immune system, 23,24 we found that pharmacological regulation of the innate immune system benefited transplanted cell engraftment. It is noteworthy that the major fraction of transplanted hepatocytes is cleared intravascularly even before cells enter the liver parenchyma.…”
Section: Discussionmentioning
confidence: 80%
“…7B, 7C). Furthermore, in mDCs and monocytes short-term inhibition of mTOR clearly enhances various inflammatory molecules and processes needed for an effective inflammatory and immune response, such as NF-kB, IL-12, CD86, IL-1b, or Ag presentation, whereas it inhibits classical anti-inflammatory molecules like IL-10, PD-L1, or STAT3 (33,34,67) (Fig. 8).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of overall bacterial infection was significantly higher in everolimus-treated transplant patients than in azathioprine-treated patients (6). Rapamycin has potent antimigratory and antiproliferative effects and is associated with a dysregulation of the innate immune response, including a decrease in interleukin-10 gene transcription (12). Thaunat et al reported two cases of pulmonary infection caused by Mycobacterium xenopi during sirolimus therapy (19).…”
mentioning
confidence: 99%